Discrete Four-Order Schrödinger Equation on the Hexagonal Triangulation (Journal of Mathematical Study, 2025)
In this paper, we establish a decay estimate for the discrete four-order Schrödinger equation on the hexagonal triangulation with $γ$=0. The proof is based on the uniform estimates of oscillatory integrals, as developed by Karpushkin, along with a key result by Varchenko. Our result is to show the $l^1$→$l^∞$ dispersive decay rate is $⟨t⟩^{−σ}$ for any $0
Keywords: Schrödinger equation; graph; Strichartz estimate